2-Methoxy-5((3, 4, 5-trimethosyphenyl)seleninyl) phenol inhibits MDM2 and induces apoptosis in breast cancer cells through a p53-independent pathway. Issue 1 (1st December 2016) - Xu, Jingwen; Han, Mengting; Shen, Jiwei; Guan, Qi; Bai, Zhaoshi; Lang, Binyue; Zhang, Huijuan; Li, Zengqiang; Zuo, Daiying; Zhang, Weige; Wu, Yingliang
Abstract: 2-Methoxy-5((3, 4, 5-trimethosyphenyl)seleninyl) phenol (SQ) is a novel synthesized combretastatin A-4 (CA-4) analog that can be classified as a microtubule inhibitor. Our previous study demonstrated that SQ induced G2/M phase arrest and promoted apoptosis progression in breast cancer cells. In the present study, we found that SQ dissociated the MDM2-p53 complex and directly induced MDM2 degradation through the ubiquitin-dependent proteasome pathway in MCF-7 and MDA-MB-231 cells. Further, p53 was activated by SQ through regulation of its transcription, translation, and post-translation modification. More specifically, we demonstrated that SQ induced caspase-dependent but p53-independent apoptosis, and this apoptosis is associated with the inhibition of MDM2. We also showed that SQ exhibited superior in vivo efficacy and low toxicity than CA-4. The immunofluorescence histochemistry study indicated that SQ also inhibited MDM2 expression in vivo . In summary, we report for the first time that SQ shows excellent anti-breast cancer activity in vivo and in vitro and induces p53-independent apoptosis, which is associated with MDM2 inhibition. Therefore, the novel compound SQ has potential for therapeutic treatment of both wild-type and mutant p53 breast cancer. Highlights: SQ dissociates the MDM2-p53 complex and directly induces MDM2 degradation. SQ degrades MDM2 through ubiquitin-dependent proteasome pathway. SQ induces caspase-dependent but p53-independent apoptosis. SQ exhibits superior in vivo efficacy and low toxicity compared with CA-4.